Natural and synthetic biomedical polymers - Kumbar, Sangamesh; Laurencin, Cato T.; Deng, Meng (Elsevier Science, 2014)
"Polymer scientists have made an extensive research for the development of biodegradable polymers which could find enormous applications in the area of medical science. Today, various biopolymers have been prepared and utilized in different biomedical applications. Despite the apparent proliferation of biopolymers in medical science, the Science and Technology of biopolymers is still in its early stages of development. Tremendous opportunities exist and will continue to exist for the penetration of biopolymers in every facet of medical science through intensive Research and Development. Therefore, this chapter addresses different polymerization methods and techniques employed for the preparation of biopolymers. An emphasis is given to cover the general properties of biopolymers, synthetic protocols and their biomedical applications. In order to make the useful biomedical devices from the polymers to meet the demands of medical science, various processing techniques employed for the development of devices have been discussed. Further, perspectives in this field have been highlighted and at the end arrived at the conclusions. The relevant literature was collected from different sources including Google sites, books and reviews"--